Lessons from a phenotypically normal infant with uniparental isodisomy of chromosome 21: a Case Report and review - Zhu, Yuying; Wu, Ke; Jiang, Cuicui; Zhu, Qiumin (Frontiers in Genetics, 2025)
Uniparental disomy (UPD) occurs when both homologous chromosomes are inherited from a single parent. To date, the UPD of all autosomes and the X chromosome has been recorded. A few cases of UPD of chromosome 21 have been documented. At 15 weeks of gestation, a 25-year-old pregnant woman’s non-invasive prenatal screening revealed a high risk of trisomy 21. Although no anomalies were detected in the fetal ultrasonography, amniocentesis was performed, and the fetal karyotype analysis was found normal. A single-nucleotide polymorphism (SNP) array revealed that the fetus had the copy-neutral region of homozygosity (ROH) in the long arm of chromosome 21. Subsequently, single whole-exome sequencing was performed due to the risk of recessive gene variants in ROH, and no homozygous like pathogenic or pathogenic variants were found on the long arm of chromosome 21. After genetic counseling, the parents decided to continue this pregnancy. At 37 weeks of gestation, a live male infant was delivered by Cesarean section. Copy number variation sequencing showed that the placental tissue was mosaic for trisomy 21. At the final follow-up evaluation, the 6-month-old boy had a normal phenotype.